Tantangan dan Peluang dalam Pengembangan Desa Wisata Pedesaan: Studi Kasus Desa Ngargoretno, Indonesia: Challenges and Opportunities in Developing Rural Tourism Villages: A Case Study of Ngargoretno Village, Indonesia - Muryanti Muryanti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
The development of rural tourism villages has emerged as a significant alternative in transforming subsistence agriculture patterns in rural areas, often characterized by irregular income streams that barely sustain basic needs. The trend of rural tourism village development is observed in many subsistence farming communities, leveraging the unique potential of natural and cultural resources that can be tapped through village fund utilization. The initiation of rural tourism village development in Ngargoretno Village began with community-driven efforts and a communal spirit to realize the concept of such a village. The village authorities also provided support by allocating village funds and empowerment activities, including training sessions for the youth who play a pivotal role in driving rural tourism village development. This research aims to describe the collaborative efforts between the community and village authorities in realizing rural tourism villages and identify the success factors in rural tourism village development. This research adopts a qualitative approach, with data collection conducted through observations and interviews with key stakeholders from the community and village authorities involved in rural tourism village development. The theoretical foundation of this research lies in empowerment theory, emphasizing the involvement of various stakeholders, including village authorities, educational institutions, and community organizations in rural tourism village development. The findings reveal active community involvement in infrastructure development such as roads, enhancement of tourist attractions through cleaning and painting marble, and the establishment of public facilities such as toilets. Furthermore, partnerships with educational institutions like Universitas Gadjah Mada and the Magelang Tourism Office have enriched tourism packages by introducing additional attractions such as tea plantation tours and religious tourism and promoting local cuisine. The development of rural tourism villages is also expected to increase the income of Ngargoretno Village residents through a rise in tourist visits from outside the village and the creation of new employment opportunities for the younger generation. Optimism persists, fueled by the enthusiastic spirit of village authorities and the community in developing the concept of rural tourism villages.